Positive plant and bird diversity response to experimental deer population reduction after decades of uncontrolled browsing. Issue 3 (5th November 2015) - Chollet, Simon; Padié, Sophie; Stockton, Stephen; Allombert, Sylvain; Gaston, Anthony J.; Martin, Jean‐Louis
Abstract: Aim: During the 20th century, deer (family Cervidae ), both native and introduced populations, dramatically increased in abundance in many parts of the world and became seen as major threats to biodiversity in forest ecosystems. Here, we evaluated the consequences that restoring top‐down herbivore population control has on plants and birds. Location: Forest ecosystems of Haida Gwaii (British Columbia, Canada) where introduced black‐tailed deer ( Odocoileus hemionus ) have dramatically limited tree regeneration and simplified understorey plant, insect and bird assemblages. Methods: We experimentally assessed ecosystem‐wide responses of plant and bird communities to a 80% reduction of deer abundance on two medium‐sized islands (146 and 249 ha). We monitored changes in plant and bird communities for the 13 years following the start of culling and used two islands without culling and a set of exclosures as controls. Results: Native plant communities increased in cover and richness after culling, while introduced plants decreased. Birds that depend on understorey vegetation for feeding and/or breeding increased significantly after deer were reduced in abundance but species not dependent on understorey vegetation did not. Finally, on control islands, plant and bird communities were stable or declined throughout the study period. Main conclusions: Biodiversity losses caused by current continental‐scale trends of increasing deer populations are potentially reversible. We demonstrate that controlling large herbivore populations (native or introduced) offers significant conservation benefits to forest understorey plant communities, even to those most negatively affected by uncontrolled browsing. We also report, for the first time, strong evidence that higher trophic levels (birds) can respond rapidly and positively to herbivore density control.